Jezični krajobraz naselja Martinaca - Bockovac, Timea; Simara, Patricia (SlavVaria, 2026)
The linguistic landscape of the settlement Martinci. The linguistic landscape of the settlement Martinci (Hungarian: Felsőszentmárton) in Hungary, where a significant number of Croats live, reflects the layered language situation of the minority community within the majority environment. In Martinci, the Croatian language has a visible presence in public signs, which confirms the persistence of the Croatian minority and their desire to preserve their language and identity. The research on the linguistic landscape of Martinci is based on the collection, classification, and analysis of signs present in the public space. The linguistic accuracy in the signs varies, but this landscape reflects the importance of the visibility of the minority language, which is maintained as a symbol of ethnic identity and cultural heritage. Local signs and the public use of language serve as key elements of this visibility and the linguistic presence of the minority.